Mitigating Turnover Intention through Organization Development Interventions: An Action Research on Healthcare Professionals in Bangkok - Thitatorn, Panisara; Wisankosol , Papitchaya (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study examines the key determinants of employee turnover intention and evaluates the impact of Organizational Development Interventions (ODIs) in mitigating turnover intention among healthcare professionals in Bangkok. Conducted using an action research approach, the study involved 250 participants; nurses, doctors, and administrative staff, and was carried out in three phases: pre-ODI assessment, ODI implementation, and post-ODI evaluation. Data were collected through validated surveys measuring job satisfaction, motivation, work-life balance, leadership style, and turnover intention. Multiple Linear Regression (MLR) analysis revealed that all four organizational factors were significant negative predictors of turnover intention. In response, a set of targeted ODIs including job enrichment programs, wellness initiatives, and leadership training were implemented. Post-intervention analysis using Paired Sample t-tests showed significant improvements in job satisfaction, motivation, work-life balance, and leadership style, alongside a marked reduction in turnover intention. Effect size (Cohen’s d) calculations further confirmed the practical significance of these changes. The results highlight the effectiveness of tailored, multi-dimensional ODIs in improving retention and workplace satisfaction among healthcare professionals. This study contributes valuable insights to organizational development practices within the healthcare sector in Southeast Asia